Design of Integer Order Approximation Fractional Order Controller with for Automatic Voltage Regulation System - Yildirim, Burak; Ozdemir, Mahmut Temel; Eke, Ibrahim (Ieee, 2019)
Maintaining the voltage value, which is one of the most important parameters of electrical power systems, is vital for modern power systems. In this study, the application of an Integer Order Approximation Fractional Order (IOAFO) controller to an automatic voltage regulation (AVR) system is shown. Matlab/Simulink model was developed for AVR system controlled by IOAFOPI, which is formed by using continued fractional expansion method (CFE) and the performance of IOAFOPI was compared with classical PID. Ant Colony Optimization (ACO) method was used to obtain controller gains in the analysis studies. A multi-purpose cost function consisting of important properties of both time domain and frequency domain was used to perform the optimization of the models. The results obtained in the analysis for the purposed IOAFOPI controller were compared with the classical PID for both time domain and frequency domain responses. The stability of the controllers against system uncertainties are also shown in the results.
4th International Conference on Power Electronics and their Applications (ICPEA) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: Automatic Voltage Regulation; Integer Order Approximation Fractional Order Controller; Ant Colony Optimization; Multi Objective Cost Function